The Entrepreneur Opinion Towards Behavior of Chinese Tourists Traveling in Thailand - Tangtenglam, Susaraporn (Dusit Thani College Journal, 2020)
The purpose of this study was to study The Entrepreneur opinion towards behavior of chinese tourists traveling in Thailand. The sample consisted of 300 tourism, entrepreneur tour guides 50 people, hotel operators 50 people, Souvenir shop 50 people operator Restaurant 50 people operator Tour 50 people Operators Car Rental 50 people by questionnaire. Quantitative data analysis The data collected from the data collection method were used. The above steps include analyzing the personal factors of the respondents. And attitude towards Chinese tourist behavior. Descriptive statistics include percentage. The results showed that The Entrepreneur opinion Towards Behavior of Chinese Tourists Traveling in Thailand .Expenses for travel in Thailand exclude airfare. Most of them are 4,001 Yuan, accounting for 38.64 percent, followed by 2,001 - 3,000 Yuan. in the Bangkok Metropolitan Administration (91.26%), followed by Phra Nakhon Si Ayutthaya (32.4%), or the majority of the 67.53%. 25.44 percent of souvenirs bought back from Thailand. buy dried souvenirs, such as processed 29.52%. Most of them get information about tourist destinations in Thailand. 43.1 percent. The majority of travel in Thailand is traveling 83 percent. 85, followed by self travel 15.24%.